Collaborative Governance Dalam Pengelolaan Himpunan Petani Pemakai Air Desa Gedongarum Kecamatan Kanor Kabupaten Bojonegoro - Aurellia, Emily; Taufiq, Ahmad; Kasiami, Sri (UNIVERSITAS MUHAMMADIYAH MATARAM, 2023)
The purpose of this study is to determine the cooperation beetwen stakeholders under the leadership of the Water User Farmers Assosiation (HIPPA) in Gedongarum village, Kanor district, Bojonegoro local government. The study uses a descriptive method with a qualitative focus. This theory used in this research is according to Ansell & Gash (2008) with main indicator, namely : starting condition, institutional planning, enabling leadership and collaboration processes. This result of research show that the collaboration carried out in the management of the Water User Farmers Assosiation (HIPPA) is very well established and stakeholders can build a sense of competitive trust and have strong commintment to developing each program owned by each actor in accordance with goals of the collaboration. Which has been mutually agreed upon.